Using multimedia to teach Arabic literature - Ahmad H.Osman, Rahmah (2010)
In the context of the Malaysian native Malay language speaker, learning Arabic literature, specifically poetry as a second or a foreign language, no specific research was found as well as in teaching Arabic poetry, i.e; classical to the Malaysian non-native speaker, ie:, via multimedia sources no specific research was found. However in the teaching of language context, numerous studies were found in the use of multimedia as well as non multimedia arenas. This is however not the scope of this study as it assumes that the target group has this type of elementary language base in order to progress to literature studies. Poetry has been used in many forms in the teaching of Arabic language. It has been highlighted as being the link to fill the cultural void in teaching language. Learners thus experience the culture of the language and therefore relate to the language much more than just memorizing vocabulary, syntax and grammatical rules. Literature in general has also been discussed in the context of developing critical, analytical skills in the foreign learner of a language. It is however complex for second and foreign learners of that language. It therefore requires specific tools i.e. language tools geared to the literature context in order to facilitate the grasping of a literary work. The learning and teaching of literature also has its specific inherent problems which are not covered in that of linguistics teaching. A specific problem based theory which can discuss these issues to bridge the gap in literary understanding is a necessity. Thus in the teaching of literature it is optimum to have a preparatory phase, which provides linguistic activities and establishes comprehension, an interpretive phase, which includes expression and exchange of student reactions and a synthesis phase, which provides for an overall evaluation of the text. Hence, this study concentrates on formulating the tools necessary for these skills to be acquired, tailor made for the Malaysian student studying Arabic poetry, designed to increase their analytical ability in the Arabic language. The presentation of this in a multimedia package is to promote motivation and take the monotony out of the memorization text based context. This will also encourage independence and instill a level of confidence to take the challenge of Arabic literature.